Effective Learning Strategies in Improving Students’ Academic Achievement at MTSN 2 in Bandung City - Sulastri Neneng (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2025)
This study aims to analyze effective learning strategies implemented by teachers to improve students’ academic achievement at MTSN 2 in Bandung City. The research employs a qualitative descriptive approach, focusing on the observation of classroom practices, teacher interviews, and document analysis. The findings reveal that effective learning strategies applied by teachers include active learning, cooperative learning, and contextual teaching methods that encourage student participation and critical thinking. The integration of digital media and interactive learning environments also plays a significant role in enhancing student engagement and comprehension. Moreover, teachers’ pedagogical competence and their ability to adapt strategies to students’ characteristics contribute to better learning outcomes. The study concludes that the success of effective learning strategies depends on the synergy between innovative teaching methods, student-centered learning environments, and continuous evaluation. These strategies are proven to have a positive impact on students’ motivation, understanding, and academic achievement in Islamic junior high schools (MTSN 2) in Bandung City.